Фольклор у сучасній македонській драматургії - Петровська Кузманова, К. (Народна творчість та етнографія, 2009)
The authors that were writing Macedonian drama from the end of sixties of the twentieth century use the archetipical and mythological symbolizm in a way that is close to the European theatrical tendencies. In the texts of «Jane Zadrogaz», «The miracle of St. Georges», «Masks» etc. the folklore is brought on stage transformed and put in a new function. Analysing those texts we can say that the folklore matrixes in contemporary Macedonian play are not only an illustration, but the authors use the signs and the elements of the folklore in a sense of contemporary experience of the world. The authors such as Stefanovski, Chingo, Bogdanovski and others took different approaches to this matter and have more or less succeeded to create the picture of the world according to the folklore model, and the level of success in this concept often depended on the way of approaching the material and of the individual creative abilities.